Física moderna: proposta de abordagem do efeito fotoelétrico no Ensino Superior - SOUZA, Elyson Robson Dias de Souza e (2020)
The approach to topics of Modern and Contemporary Physics (FMC) in Physics classes in Higher Education is still the subject of debates and discussions among researchers in the area. Although nowadays its importance for the technologies that we find in our daily life is recognized, we still observe numerous problems to deal with this theme in the classroom. Several factors influence the approach of FMC in Higher Education, starting with the training of teachers for the subject, lack of time to apply an extensive curriculum and traditional classes that are of no interest to students. In view of this perspective, the present work proposes some didactic resources different from the usual ones, aiming to facilitate the work of the teacher and a way to encourage the student for FMC matters. To this end, we will deal with the Photoelectric Effect through its history, from the context of light to its applicability today, using a low-cost experiment - a homemade electroscope and a source of ultraviolet radiation - in addition to a proposal for applying the simulation. of the Photoelectric Effect on the Vascak website, seeking to achieve active and meaningful learning in the classroom.